ANALISIS KELAYAKAN PENGEMBANGAN USAHA BAWANG GORENG DZ KHAS LANDE DI DESA GERAK MAKMUR KECAMATAN SAMPOLAWA KABUPATEN BUTON SELATAN - Wa Ode Hasna; Idrus Salam; Fahria Nadiryati (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to (1) analyze the feasibility of non-financial aspects (market and marketing aspects, technical and technological aspects) of the DZ Khas Lande Fried Onion business in Gerak Makmur Village, Sampolawa District, South Buton Regency, (2) analyze the financial aspects with the criteria (NPV, Net B/C, IRR, PP and sensitivity analysis) DZ Khas Lande Fried Onion business in Gerak Makmur Village, Sampolawa District, South Buton Regency. The sample determination in this research was carried out using a non-probability sampling method, namely by making 2 business owners and 3 employees as respondents. The research results look at the market and marketing aspects of businesses that have market opportunities and a marketing mix that is quite adequate. The technical aspects include reviewing the business location, production area, equipment and production processes that meet the operational standards for the production of DZ Khas Lande Fried Onions. Then viewed from the financial aspect with criteria, the NPV value is Rp. 27,722,168,-, with a discount factor of 10%, the Net B/C is 2, the IRR value is 32.27% and the Payback Period (PP) is obtained with a term of long investment return period of 1 year 2 months. This business, viewed from non-financial and financial aspects, is declared worthy of development. In addition, based on sensitivity analysis, the business remains viable even though there is an increase in input costs of 5% and a decrease in output prices of 5%. However, if there is an increase in input costs of 5% and a decrease in output prices of 5% simultaneously, then the DZ Khas Lande fried onion business is not feasible to run.